Mitotic and apoptotic activity in colorectal neoplasia - Kohoutova, Darina; Pejchal, Jaroslav; Bures, Jan (BMC gastroenterology, 2018)
BACKGROUND: Colorectal cancer (CRC) is third most commonly diagnosed cancer worldwide. The aim of the prospective study was to evaluate mitosis and apoptosis of epithelial cells at each stage of colorectal neoplasia. METHODS: A total of 61 persons were enrolled into the study: 18 patients with non-advanced colorectal adenoma (non-a-A), 13 patients with advanced colorectal adenoma (a-A), 13 patients with CRC and 17 controls: individuals with normal findings on colonoscopy. Biopsy samples were taken from pathology (patients) and healthy mucosa (patients and healthy controls). Samples were formalin-fixed paraffin-embedded and stained with haematoxylin-eosin. Mitotic and apoptotic activity were evaluated in lower and upper part of the crypts and in the superficial compartment. Apoptotic activity was also assessed using detection of activated caspase-3. RESULTS: In controls, mitotic activity was present in lower part of crypts, accompanied with low apoptotic activity. Mitotic and apoptotic activity decreased (to almost zero) in upper part of crypts. In superficial compartment, increase in apoptotic activity was observed. Transformation of healthy mucosa into non-a-A was associated with significant increase of mitotic activity in lower and upper part of the crypts and with significant increase of apoptotic activity in all three compartments; p < 0.05. Transformation of non-a-A into a-A did not lead to any further significant increase in apoptotic activity, but was related to significant increase in mitotic activity in upper part of crypts and superficial compartment. A significant decrease in apoptotic activity was detected in all three comparments of CRC samples compared to a-A; p < 0.05. No differences in mitotic and apoptotic activity between biopsies in healthy controls and biopsy samples from healthy mucosa in patients with colorectal neoplasia were observed. Detection of activated caspase-3 confirmed the above findings in apoptotic activity. CONCLUSIONS: Significant dysregulation of mitosis and apoptosis during the progression of colorectal neoplasia, corresponding with histology, was confirmed. In patients with sporadic colorectal neoplasia, healthy mucosa does not display different mitotic and apoptotic activity compared to mucosa in healthy controls and therefore adequate endoscopic/surgical removal of colorectal neoplasia is sufficient.
Keywords: Caspase 3; kaspasa 3; karcinom; biopsie; Mitosis; Adult; senioři; Aged; Male; adenom; střevní sliznice; apoptóza; lidé; lidé středního věku; Humans; Enzyme Activation; Middle Aged; Colorectal carcinoma; mitóza; Apoptosis; senioři nad 80 let; Colorectal Neoplasms; Aged, 80 and over; Intestinal Mucosa; mužské pohlaví; Colorectal adenoma; dospělí; kolorektální nádory; Biopsy; prospektivní studie; aktivace enzymů; ženské pohlaví; Female; Adenoma; Prospective Studies; Carcinoma